Strategi Program “Mentari Cafe” pada Pasien Skizofrenia di Instalasi Rehabilitasi Psikososial Rumah Sakit Dr. Soeharto Heerdjan, Jakarta - Cahyani Mekarsari, Tria; Hanafi Rochman, Uut; Trustisari, Hastin; Esti Winahayu, Neng (NHM PRESS, 2024)
Currently, there are 24 million people in the world with schizophrenia. People with schizophrenia need rehabilitation to improve their social functioning. One of the programs available at the Psychosocial Rehabilitation Installation of Dr. Soeharto Heerdjan Hospital is “Mentari Cafe”. This study aims to determine the strategies used in the “Mentari Cafe” program provided to schizophrenia patients. The method used is descriptive qualitative, data collection is done through interviews, observations, and documentation studies. The results showed that there were strategies used to make the “Mentari Cafe” program effective for schizophrenia patients. The strategies carried out in implementing the “Mentari Cafe” program are making program implementation guidelines, gradual learning, and working with families to support patients during the “Mentari Cafe” program. Approaching and motivating is one of the approaches suggested to overcome the patient's lack of initiative during the “Mentari Cafe” program.